A REVIEW ON DATA MANAGEMENT IN CLOUD COMPUTING - HASSAN, MUHSIN (Journal of Information Systems and Digital Technologies, 2022)
The present cloud computing time opens another road for organizations to consider moving their information data management solutions to the cloud. It is demonstrated through recent successful deployments that data management applications are one of the most suitable candidates for deployment in the cloud. Data management in cloud Computing brings many challenges as well as advantages. This paper represents the current state of data management solutions in the cloud and the current direction of research in Data management in Cloud Computing. It is necessary to contemplate that cloud-based data management is a very fluid field, which means technologies are changing rapidly. It is also important that the industry is investing more as compared to other fields of data management, thus making an interesting subject for detailed study.